REPORT OF THE ANNUAL CONVENTION. - Walgenbach, Paul H. (The Accounting Review, 1961)
This article presents information on the 60th annual meeting of the American Accounting Association. The meeting was held during August 29-31 on the campus of the Ohio State University, Columbus, Ohio. It was one of the largest and most successful conventions of the Association. At the Plenary sessions on Tuesday and Wednesday, the following speakers discussed the topics indicated: H.G. Nelson, Ford Motor Company, William W. Werntz. The following subjects were discussed at the round tables held on Tuesday and Wednesday: "The Ford and Carnegie Reports," "Accounting Research," "Scope and Content of the Filth Year of Collegiate Education for Accounting," "Recent Developments in Income Tax Legislation and Education," "Integration of Managerial Accounting into Traditional Accounting Courses," "Television and Accounting Instruction," "Mathematics and Accounting Instruction," "Certified Public Accountant Regulations and Accounting Curricula," "Professional Development of Accounting Personnel in Government Service," "Scope and Content of First Course in Cost Accounting," Accounting Developments Abroad."